2015
DOI: 10.1039/c5dt03753k
|View full text |Cite
|
Sign up to set email alerts
|

Cyclometalated Ir(iii) complexes of deprotonated N-methylbipyridinium ligands: effects of quaternised N centre position on luminescence

Abstract: Six new tricationic Ir(III) complexes of cyclometalating ligands derived from 1-methyl-2-(2'-pyridyl)pyridinium or 1-methyl-4-(2'-pyridyl)pyridinium are described. These complexes of the form [Ir(III)(C^N)2(N^N)](3+) (C^N = cyclometalating ligand; N^N = α-diimine) have been isolated and characterised as their PF6(-) and Cl(-) salts. Four of the PF6(-) salts have been studied by X-ray crystallography, and structures have been obtained also for two complex salts containing MeCN and Cl(-) or two Cl(-) ligands ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 86 publications
3
14
0
Order By: Relevance
“…Overall, the three N atoms of N3C chelates are arranged in the meridional mode, while the phenyl appendage is located at the axial site vs the plane defined by the meridional arranged N atoms and is located at the trans disposition to the unique chloride, leaving the monodentate N donor to occupy the remaining coordination site that is trans to the central pyridine unit of N3C chelate. The unique Ir−C distances of 2.005(4) Å in 3 and 2.015(5) Å in 5 are similar to the reported Ir−C bond distances trans to the chloride, 37 while the py and mpzH ligands of 3 and 5 exhibited the longest Ir− N distances within each molecule, i.e., 2.067(3) and 2.052(4) Å, which could be due to the strong trans influence exerted by the central pyridine unit of the N3C chelate, which exhibited the shortest Ir−N distance, i.e., 2.007(3) and 2.005(4) Å.…”
Section: ■ Results and Discussionsupporting
confidence: 81%
“…Overall, the three N atoms of N3C chelates are arranged in the meridional mode, while the phenyl appendage is located at the axial site vs the plane defined by the meridional arranged N atoms and is located at the trans disposition to the unique chloride, leaving the monodentate N donor to occupy the remaining coordination site that is trans to the central pyridine unit of N3C chelate. The unique Ir−C distances of 2.005(4) Å in 3 and 2.015(5) Å in 5 are similar to the reported Ir−C bond distances trans to the chloride, 37 while the py and mpzH ligands of 3 and 5 exhibited the longest Ir− N distances within each molecule, i.e., 2.067(3) and 2.052(4) Å, which could be due to the strong trans influence exerted by the central pyridine unit of the N3C chelate, which exhibited the shortest Ir−N distance, i.e., 2.007(3) and 2.005(4) Å.…”
Section: ■ Results and Discussionsupporting
confidence: 81%
“…Also, [Ir(Me-2,2′-bpy) 2 (bpy)] 3+ and [Ir(Me-3,2′-bpy) 2 (dCF 3 bpy)] 3+ were chosen from a series of highly water soluble Ir( iii ) cyclometalated complexes ( Scheme 3 ). 46 , 47 [Ru(bpy) 3 ] 2+ was employed as a control standard, and Cl – salts were used in all cases. In each case, reactions were performed with cyclohexen-2-one as the enzyme oxidative substrate.…”
Section: Resultsmentioning
confidence: 99%
“…There have been few investigations on the influence of the substitution position of ligand functionalities on the properties of [Ir(C^N) 2 (N^N)] + complexes. Examples include the introduction of diphenylamino, 25 fluoro, 26 methyl, 27 trifluoromethyl, 28,29 methylpyridinium, 30 bromo and fluorenyl 31 and benzylsulfonyl 15 groups in the 3-, 4-and 5-positions of the cyclometallating phenyl ring. In all of these studies, except for the one investigating bromo and fluorenyl groups, 31 it was found that substitution in the 4-position, i.e.…”
Section: Introductionmentioning
confidence: 99%